Metabonomic analysis of toxic action of long-term low-level exposure to acrylamide in rat serum. (December 2018) - Cao, C; Shi, H; Zhang, M; Bo, L; Hu, L; Li, S; Chen, S; Jia, S; Liu, YJ; Liu, YL; Zhao, X; Zhang, L
This study assessed the effects of long-term, low-dose acrylamide (AA) administration in rats using ultra-performance liquid chromatography–mass spectrometry. Forty male Wistar rats were randomly divided into the following four groups: control, low-dose AA (0.2 mg/kg BW), middle-dose AA (1 mg/kg BW), and high-dose AA (5 mg/kg BW). AA was administered to rats via drinking water ad libitum. After 16-week treatment, rat serum was collected for metabonomic analysis. Biochemical tests were further conducted to verify metabolic alterations. Eleven metabolites were identified with significant changes in intensities (increased or reduced) as a result of treatment. These metabolites included citric acid, pantothenic acid, isobutyryl-l -carnitine, eicosapentaenoic acid, docosahexaenoic acid, sphingosine 1-phosphate, LysoPC(20:4), LysoPC(22:6), LysoPE(20:3), undecanedioic acid, and dodecanedioic acid. Results indicate that chronic exposure to AA at no observed adverse effect level does not exert a toxic effect on rats at the body metabolism level. AA disturbed the metabolism of lipids and energy, affected the nervous system of rats, and induced oxidative stress and liver dysfunction.